2023
DOI: 10.1186/s40359-023-01066-w
|View full text |Cite
|
Sign up to set email alerts
|

The sound of stress recovery: an exploratory study of self-selected music listening after stress

Abstract: Background Empirical support for the notion that music listening is beneficial for stress recovery is inconclusive, potentially due to the methodological diversity with which the effects of music on stress recovery have been investigated. Little is presently known about which recovery activities are chosen by individuals for the purpose of stress recovery, and whether audio feature commonalities exist between different songs that are selected by individuals for the purpose of stress recovery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…Using various instruments, AMT activates different brain regions, thus enhancing cognitive functions and promoting neural plasticity [9,45,49]. Moreover, our NMA suggests that LtM has a mild effect on improving depressive symptoms in dementia patients (SMD = −0.26), corroborating research that highlights the stress-reducing properties of music interventions [62,63]. Soothing melodies, such as classical music or nature sounds, help create a peaceful environment, facilitating mental and physical relaxation and offering physiological benefits like reduced heart rate and blood pressure [47,63].…”
Section: Possible Interpretations Of Observationssupporting
confidence: 80%
“…Using various instruments, AMT activates different brain regions, thus enhancing cognitive functions and promoting neural plasticity [9,45,49]. Moreover, our NMA suggests that LtM has a mild effect on improving depressive symptoms in dementia patients (SMD = −0.26), corroborating research that highlights the stress-reducing properties of music interventions [62,63]. Soothing melodies, such as classical music or nature sounds, help create a peaceful environment, facilitating mental and physical relaxation and offering physiological benefits like reduced heart rate and blood pressure [47,63].…”
Section: Possible Interpretations Of Observationssupporting
confidence: 80%
“…Consequently, music can help regulate the neurological and physiological mechanisms that contribute to stress [11]. Research has also shown that listening to music is more effective than silence or audio control in helping people recover from stress-related symptoms such as heart rate, blood pressure, anxiety, and mood swings [12].…”
Section: Introductionmentioning
confidence: 99%